Literature Review of IoT on High School Students’ Reading Interests - Herawati, Netti; Lestari, Neta Dian (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to evaluate the effect of implementing Internet of Things (IoT) technology in library services on students’ reading interest at SMA Ilir Timur 1 Palembang. IoT provides ease in accessing information through features such as automatic borrowing, preference-based recommendations, and real-time collection management. However, despite increasing accessibility, students’ reading interest is still relatively low, influenced by the dominance of digital entertainment. Literature review shows that IoT has great potential to improve library service efficiency and student engagement, but its impact on reading interest is not yet fully significant. Therefore, this study recommends the development of an IoT strategy that is more integrated with local needs and digital literacy training for students and teachers. With an inclusive and adaptive approach, the implementation of IoT is expected to support an increase in students’ reading interest evenly in the digital era.